Understanding the Verbal Language and Structure of End-User Descriptions of Data Visualizations - Lee, Bongshin; riche, Nathalie henry; Czerwinski, Mary; Henry Riche, Nathalie (ACM Conference on Computer-Human Interaction, 2012)
Tools exist for people to create visualizations with their data; however, they are often designed for programmers or they restrict less technical people to pre-defined templates. This can make creating novel, custom visualizations difficult for the average person. For example, existing tools typically do not support syntax or interaction techniques that are natural to end users. To explore how to support a more natural production of data visualizations by end users, we conducted an exploratory study to illuminate the structure and content of the language employed by end users when describing data visualizations. We present our findings from the study and discuss their design implications for future visualization languages and toolkits.